120k views
4 votes
Y=2X+2, y=0 substitution ​

User Jones
by
5.3k points

2 Answers

7 votes

Answer:

For y = 0, x = -1

Explanation:


\text{Put the value of }\ y=0\ \text{to the given equation}\ y=2x+2:\\\\0=2x+2\qquad\text{subtract}\ 2x\ \text{from both sides}\\\\0-2x=2x-2x+2\\\\-2x=2\qquad\text{divide both sides by (-2)}\\\\(-2x)/(-2)=(2)/(-2)\\\\x=-1

User Radato
by
5.0k points
4 votes

Answer:

Solving equations by substitution is exactly as it says it is, you will simply substitute.

In your example: y=2x+2, y=0

You will plug 0 in for y

Your equation will now look like 0=2x+2, now you are going to solve it like a normal equation, getting x by itself

0=2x+2 (first you want to minus 2 from each side)

-2=2x (now you are going to divide each side by 2)

-1=x

x=-1

Hope this helps ;)

Explanation:

User Vitruvius
by
4.9k points